PENGARUH BRAND IMAGE, BRAND TRUST, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN PRODUK EMINA COSMETICS PADA MAHASISWI FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SATU TULUNGAGUNG ANGKATAN TAHUN 2018 - Ina Safitri; Ali Mauludi (Bajang Institute, 2022)
The development of the cosmetic industry in Indonesia is growing rapidly. This has led to intense business competition between cosmetic companies to attract consumers’ attention. One of the consumers of cosmetic product is a college student. College student also have considerations before choosing the cosmetic products to used. This study aims to determine the effect of brand image, brand trust, price and product quality on consumer loyalty for Emina Cosmetics product on student of the Faculty Economics and Islamic Business UIN SATU Tulungagung class of 2018 batch partially and simultaneously using multiple linear regression analysis. This study uses an associative quantitative approach. The data source used is primary data by distributing questionnaires to 100 respondent who using Emina Cosmetics product with a minimum of two purchase. The results showed that brand image, price and product quality partially have a positive and significant effect on consumer loyalty for Emina Cosmetics products, while brand trust partially has a positive but not significant effect on consumer loyalty for Emina Cosmetics products. Meanwhile, brand image, brand trust, price and product quality simultaneously have a positive and significant effect on consumer loyalty for Emina Cosmetics products with a total effect of 37.7%. Keywords: Brand Image, Brand Trust, Price, Product Quality, Consumer Loyalty